When Black Feminism Meets Canadian Women's Studies: A Psycho-Social Analysis of Discursive Contradiction and Psychical Conflict in the Classroom - Ringrose, Jessica (Atlantis, 2007)
This paper explores how Black feminist curriculum challenges the pedagogy of Women's Studies in Canada through a psychosocial analysis of classroom observations and interview narratives. The difficulties experienced by white women and the traumatic effects for black women in negotiating discursive contradictions that emerge in the wake of inserting Black feminism into Women's Studies are examined.